Learning from the veg box: designing unpredictability in agency delegation - Verame, Jhim Kiel M.; Costanza, Enrico; Fischer, Joel E.; Crabtree, Andy; Ramchurn, Sarvapali D.; Rodden, Tom; Jennings, Nicholas R. (2018)
The Internet of Things (IoT) promises to enable applications that foster a more efficient, sustainable, and healthy way of life. If end-users are to take full advantage of these developments we foresee the need for future IoT systems and services to include an element of autonomy and support the delegation of agency to software processes and connected devices. To inform the design of such future technology, we report on a breaching experiment designed to investigate how people integrate an unpredictable service, through the veg box scheme, in everyday life. Findings from our semi-structured interviews and a two- week diary study with 11 households reveal that agency delegation must be warranted, that it must be possible to incorporate delegated decisions into everyday activities, and that delegation is subject to constraint. We further discuss design implications on the need to support people’s diverse values, and their coordinative and creative practices.